Assessing intentions for a third child among Chinese adults: A nationwide online survey regarding China's 3-child policy. Issue 12 (24th March 2023) - Yue, Caibin; Zheng, Xiaolei; Shang, Wei; Wang, Ping; Xie, Zhaohong; Luo, Liyan; Xu, Yunyun; Li, Qing; Song, Dandan; Yue, Xinyi; Wang, Xiao; Yuan, Xue; et al.
Abstract : Aging populations, along with low fertility rates, have become a pervasive world-wide problem. To address this challenge, China issued a universal 3-child policy on May 31, 2021. However, little is known regarding the intentions of childbearing-aged Chinese for a third child. The purpose of this study was to assess the fertility intentions of the Chinese as related to this third-child policy and identify risk factors for third-child refusal. In this cross-sectional study, a total of 2129 Chinese childbearing-aged participants were recruited nationwide from June 15 to July 22, 2021. Each participant was interviewed using questionnaires to establish their sociodemographic variables, psychosocial factors as related to third-child intentions, and reasons for third-child refusal. Finally, 2115 responses (866 men and 1249 women) were analyzed. IBM SPSS Statistical Software (version 19) was used for the statistical analyses. Multivariate logistic regression analyses were used to assess independent influences for third-child refusal. Approximately 30% of these participants reported an intention for having a third child. In those expressing a refusal for a third child, women showed a higher prevalence rate (74.1 vs 63.2%, P < .001). Results from multivariate logistic regression analyses revealed that age ( P = .033), unemployment ( P = .045), and currently raising 2 children ( P = .017) were risk factors for third-child refusal among men, while age ( P < .001), >15 years of education ( P = .017), current smokers ( P = .005) and residing in Northern China ( P = .035) were risk factors for women. Overall, increased demands upon time and energy (41.5%), as well as economic burdens (41.4%), were the most prevalent reasons for the refusal of a third child, while achieving mutual care among siblings (52.5%) and reducing child educational costs (33.3%) were the most effective persuasions. In response to the 3-child policy, Chinese childbearing-aged adults showed low rates of intention for a third child, with women showing a higher prevalence of third-child refusal. The identification of risk factors and the reasons for third-child refusal as revealed from the results of this study provide a foundation for the development of programs needed to aid in the implementation of this 3-child policy.